Modernism and Postmodernism Concepts in Education: Its Impact on EFL Students’ Autonomy and Implication for EFL Teachers - Vahid Norouzi Larsari; Radka Wildová (Journal of English as A Foreign Language Teaching and Research, 2022)
Promoting learner autonomy is considered as a vital concern to EFL learners, so far much attempt, and related to develop learner autonomy in various concepts. The present study aimed at examining the effect of Postmodernism and Modernism concepts on EFL learners. This study carried out in the course of study at high school in Iran. Accordingly, 60 learners, between 16 and 17 years old, randomly chosen from a larger participants of 80 EFL learners with respect to their achievement on Oxford Placement Test (OPT), attending high school in Iran. The selected participants has been assigned into two groups (i.e., postmodernism and modernism concepts, respectively). Each group involved 30 participants. Control group (n=30) usual teaching through modernism concepts, whereas experimental group (n=30) is exposed to postmodernism concepts. Over the course of this present study, the data was gathered through a pre-test, and post-test of learner autonomy questionnaire. The t-test statistical procedure utilized to the research question. The findings of the result showed that postmodernism concepts significantly performed better than the modernism concepts group in the learner autonomy. The results of this study showed that all those who are engaged in language teaching and learning can process to possess a better perspective into developing efficient instructions.